Design and Implementation of an Electronic System of Salaries: (Nineveh Investment Commission as a Model) - Mohamed Alchalabi; Mafaz Alanezi (College of Education for Pure Sciences, 2021)
Electronic systems are considered one of the most important pillars in the development of the work of any institution, especially the systems related to the administrative and financial aspects. In this research, an electronic system for salaries for the Nineveh Investment Commission (NIC) was designed and implemented model using the language (C#), A central database was built using a Database Management System (SQL), This system was based on a local wireless network to share work by adopting (Client/Server) model to connect the computers, the proposed system includes very important features such as the open system data that enables the user to add and amend the percentages of the basic and secondary salary components, automatic calculation of the salary by specifying the employee service specifications and the certificate obtained, fixed and variable allocations and deductions, calculating all leave, Determining annual bonuses and promotions and organizing them to makes it easy for the user to know who is eligible, update and calculate them, in this system several levels of system users were built. A report was added for the employee's last salary certificate with detailed reports on salaries and the system was strengthened with the feature of backing up to prevent the database from Damage and referred to at any time. The system was tested on real data to issuing salary reports for three months. As the system met with great desire and reliability in its use by conducting a questionnaire to measure the usability of the system on the specialists.